Breast-conserving treatment versus mastectomy in T1-2N0 breast cancer: which one is better for Indonesian women? (Faculty of Medicine Universitas Indonesia, 2012)
Background: This study aimed to compare the treatment outcomes between the use of breast-conserving treatment (BCT) and mastectomy for T1-2N0 breast cancer patients. Methods: This study retrospectively reviewed T1-2N0 breast cancer patients who received treatment between January 2001 and December 2010 at Department of Radiotherapy Cipto Mangunkusumo Hospital and Jakarta Breast Center. The endpoints of this study were overall survival (OS), local recurrence (LR), contra-lateral breast cancer (CBC), distant metastasis (DM), and disease-free survival (DFS). Results: Among the 262 eligible patients, 200 (76.3%) patients underwent BCT while 62 (23.7%) patients underwent mastectomy. There were no differences between BCT and mastectomy groups in 5-Y OS (88.2% vs 86.7%, p = 0,743), LR (7.4% vs 2.7%, p = 0.85), CBC (3.4% vs 5.3%, p = 0.906), DM (17.7% vs 37.7%, p = 0.212), and DFS (78.5% vs 60.7%, p = 0.163). In multivariate analysis, grade 3 was associated with worse OS (HR 2.79; 95% CI 1.08 – 7.21, p = 0.03) and DFS (HR 2.32; 95% CI 1.06 – 5.06). Premenopausal women were associated with decreased risk of DM (HR 0.37; 95% CI 0.17 – 0.80) and DFS (HR 0.38; 95% CI 0.19 – 0.78). Conclusion: BCT and mastectomy showed similar outcome in terms of OS, LR, CBC, DM, and DFS. (Med J Indones. 2012;21:220-4)